Pemanfaatan Aplikasi Android Dalam Rancang Bangun Sistem Informasi Persebaran Indekos Di Wilayah Pancor Kabupaten Lombok Timur - Nur Nurhidayati; Amri Muliawan Muliawan Nur (Infotek: Jurnal Informatika dan Teknologi, 2021)
Hanzanwadi University is a private university in Selong City, East Lombok, West Nusa Tenggara. As one of the education centers for Hamzawandi University, of course, there will always be thousands of new students from various regions every year. Likewise with the distribution of boarding houses which will be the target of students who come from outside the Pancor - Selong area to look for the boarding house. A boarding house is one of the places for lodging service providers or a temporary residence. [1] Often encountered the availability of boarding rooms that are not comparable with boarding-boarding seekers is a problem for both parties (boarder and owner). Therefore boarding seekers must find information more quickly in order to get an appropriate place to live, be it in terms of room completeness or boarding price. Meanwhile, boarding house owners still do promotions manually, namely from the mouth of their mouth and usually stick the name of the boarding house in front of the boarding gate. With this problem, the researchers tried to create an android-based boarding information system to solve the problem. This android-based boarding information system is an application that can be used by newcomers from outside the Pancor - Selong area who feel confused in finding a boarding house that suits their wishes, as well as helping boarding owners in promoting their boarding houses. In its design, this application is carried out using the waterfall methodology, in which the waterfall is a system development method that begins with the analysis stage, then system design and implementation of making applications and testing it to the user. This system uses the Java programming language with programming software that utilizes Android Studio. [2]